Dynamic behavior of adjacent buildings connected by linear viscous/viscoelastic dampers. Issue 8 (10th February 2015) - Tubaldi, E.
Summary This paper analyzes the properties of the dynamic behavior of two adjacent buildings of different height connected by viscous/viscoelastic dampers located at the top of the shortest building. The adjacent structures are described through a continuum approach as two interconnected uniform shear beams. This permits to identify the set of characteristic parameters describing the building and damper properties that completely control the dynamic behavior of the system. An analytical solution is derived for solving the eigenvalue problem via complex modal analysis, and a parametric study is carried out to evaluate the influence of these characteristic parameters on the properties of the dynamic system. A reduced‐order model of the system is also developed, and simplified formulas are obtained for estimating the damping ratios of the first two modes of the coupled system. Two case studies consisting of realistic shear‐type adjacent buildings coupled by viscous dampers are finally analyzed. The estimates of the modal properties obtained by using the proposed analytical approach and a finite element formulation are compared with each other. It is shown that the proposed approach provides information useful for the preliminary design of the damper properties ensuring the optimal control against seismic loadings. Copyright © 2015 John Wiley & Sons, Ltd.